THE CHOSEN APPLICATION PROBLEMS USING IN TEACHING OF DATABASES BY DEVELOPMENT ENVIRONMENT DELPHI - BORZIKOVA, Jana (Trends in education, 2008)
The paper deals with using of applications problems in teaching of programming languages at technical faculties. The problems were chosen to prepare support for other subjects, especially I pointed to create relational database as a part of enterprise information system. There was used development environment Delphi.
Keywords: enterprise information system; relational databases; development environment Delphi